Type I natural killer T cells: naturally born for fighting - Tan Jin-quan; Xiao Wei; Wang Lan; He Yu-ling (Acta Pharmacologica Sinica, 2016)
Type І natural killer T cells (NKT cells), a subset of CD1d-restricted T cells with invariant Vαβ TCR, are characterized by prompt production of large amounts of Th1 and/or Th2 cytokines upon primary stimulation through the TCR complex. The rapid release of cytokines implies that type І NKT cells may play a critical role in modulating the upcoming immune responses, such as anti-tumor response, protection against infection, and autoimmunity. As a bridge between innate and adaptive immunity, type І NKT cells differentiate and mature upon stimulations to achieve and maintain a homeostasis. Orchestrating with other arms of adaptive immunity, type І NKT cells show strong cytotoxic effects in response to various tumors in a direct and/or indirect manner(s). This review will focus primarily on type І NKT cell development, homeostasis, and effector functions, especially in anti-tumor immunity, and followed by their potential applications in treatment of cancers.